From reception of classics to outreach: classical reception and American response to war. A case study. Part I - Rosanna Lauriola (Acta Scientiarum. Language and Culture, 2014)
This paper presents as a case study a discussion pertaining to a peculiar approach that some US scholars have applied to texts of ancient Greek literature, as a response to a specific reality that for decades has been afflicting American society: the timeless experience of war and its aftermath. It is a type of reading and re-usage of some ancient texts that can be regarded as a case of Classical Reception, which also, and almost inevitably, involves Outreach: it in fact provides a service beyond conventional limits to reach out to particular segments of the community. The analysis will be articulated into two parts: the first one will consist of (i) a theoretical overview of the status of Classical Reception Studies with a survey of a few cases as a sample of ‘how it works’, and (ii) an introduction to the above mentioned approach to classical texts to respond to the reality of modern war, such an approach that turns Classics into an important tool of outreach and therapy. The second part (forthcoming in Acta Scientiarum v.36, n.3) will consist of a detailed discussion of the ‘case study’ in terms of reception, outreach, and therapy, with an attention to the pedagogical discourse, and with a conclusion on a personal note of the author of this paper, based on a related personal experience.